Thylakoid Membrane Architecture in Synechocystis Depends on CurT, a Homolog of the Granal CURVATURE THYLAKOID1 Proteins. Issue 9 (19th August 2016) - Heinz, Steffen; Rast, Anna; Shao, Lin; Gutu, Andrian; Gügel, Irene L.; Heyno, Eiri; Labs, Mathias; Rengstl, Birgit; Viola, Stefania; Nowaczyk, Marc M.; Leister, Dario; Nickelsen, Jörg
Abstract : CurT is required for shaping the thylakoid membrane architecture in Synechocystis and mediates osmotic stress responses. Abstract: Photosynthesis occurs in thylakoids, a highly specialized membrane system. In the cyanobacterium Synechocystis sp PCC 6803 (hereafter Synechocystis 6803), the thylakoids are arranged parallel to the plasma membrane and occasionally converge toward it to form biogenesis centers. The initial steps in PSII assembly are thought to take place in these regions, which contain a membrane subcompartment harboring the early assembly factor PratA and are referred to as PratA-defined membranes (PDMs). Loss of CurT, the Synechocystis 6803 homolog of Arabidopsis thaliana grana-shaping proteins of the CURVATURE THYLAKOID1 family, results in disrupted thylakoid organization and the absence of biogenesis centers. As a consequence, PSII is less efficiently assembled and accumulates to only 50% of wild-type levels. CurT induces membrane curvature in vitro and is distributed all over the thylakoids, with local concentrations at biogenesis centers. There it forms a sophisticated tubular network at the cell periphery, as revealed by live-cell imaging. CurT is part of several high molecular mass complexes, and Blue Native/SDS-PAGE and isoelectric focusing demonstrated that different isoforms associate with PDMs and thylakoids. Moreover, CurT deficiency enhances sensitivity to osmotic stress, adding a level of complexity to CurT function. We propose that CurT is crucial for the differentiation of membrane architecture, including the formation of PSII-related biogenesis centers, in Synechocystis 6803.